STRATEGI KUALITAS HUBUNGAN MEREK, KOMITMEN, KECINTAAN TERHADAP LOYALITAS MEREK PADA RESTORAN WARALABA - Sahnaz Ubud; Suzan Ubud (Universitas Mercu Buana, 2016)
Abstract. Based on the theory of brand relationship quality and relationship marketing(RM), the aim of this research is to explore the relationship between strategy of brandrelationship quality, brand commitment, and brand love in achieving brand loyalty forforeign franchise restaurants in Malang City. Brand loyalty can be achieved if arestaurant is able to have a visionary sight on the concept of brand relationship qualitystrategy by enhancing the uniqueness, trust, delight and satisfaction for customers. Thepopulation in this study is all customers of foreign franchise restaurants in the MalangCity with 120 respondents as its sample. The sampling method used is purposivesampling; furthermore, the analysis techniques utilized in this study is PLS (PartialLeast Square). The result of this research is the brand relationship quality strategy willbe significant if it is mediated by the brand commitment and brand love. Thus, thisstudy supports the theory of brand relationship quality and relationship marketingconcepts as well as the criticisms stated by Tsai (2011). Finally, brand loyalty does notonly depend on the brand relationship quality strategy but also brand commitment andbrand love.